Thermal and Photochemical Stability Studies of Color-Converted MicroLED Microdisplay Panels - Asim M. Noor Elahi; Zengzhi Pei; Peichen Yu; Jian Xu (IEEE Photonics Journal, 2023)
The thermal and photochemical stabilities of colloidal quantum-dot (QD) nanophosphors incorporated into a blue microLED matrix by spin-cast deposition were investigated in this study. The optical characteristics of QDs-based color-converted microLEDs were also investigated in this study. The measurements performed in this work suggest the ultimate limit of QD performance in microLED devices. The findings from the stability evaluations encourage and motivate the employment of red, green QD color converters in blue microLED matrices to create full-color microLED devices. Such studies will be helpful in the design and the fabrication of high-efficiency and high-performance micro-LED microdisplay panels